Health behaviours and telomere biology in severe mental disorders - Vid Mlakar; Marta Di Forti; Els F. Halff; Deepak P. Srivastava; Ibrahim Akkouh; Srdjan Djurovic; Carmen Martin-Ruiz; Daniel S. Quintana; Viktoria Birkenæs; Nils Eiel Steen; Monica B. E. G. Ormerod; Ole A. Andreassen; et al. (Translational Psychiatry, 2026)
Abstract Alterations in telomere length (TL), a marker of cellular ageing, have been reported in individuals with severe mental disorders (SMD). Epidemiological studies of the general population have highlighted that unhealthy lifestyles may exacerbate telomere attrition. However, the impact of lifestyle on TL within the context of SMD remains unexplored. The study consisted of 410 participants (schizophrenia spectrum [ n = 225] and affective disorder [ n = 185]) collected as part of the Norwegian Thematically Organised Psychosis (TOP) study. Leukocyte TL was measured via blood and determined by quantitative real-time Polymerase Chain Reaction (qPCR). Patients provided self-report data on six lifestyle domains including: diet, exercise, smoking, alcohol consumption, substance use, and coffee consumption. A global dichotomised (healthy vs unhealthy) lifestyle variable was created, as well as a health behaviour variable, indicating the level of unhealthy behaviours. Individuals with an unhealthy lifestyle had shorter TL compared to those with a healthy lifestyle (Cohen’s d = 0.58, F = 8.62, p = 0.004). A relationship was observed between increasing number of unhealthy behaviours and shorter TL (F = 2.69, p = 0.02), adjusted for age, sex, ethnicity, trauma exposure, medication daily defined dose (DDD), years of education and diagnosis. In terms of base-pair loss, individuals with healthy lifestyles exhibited a roughly 6-year lower biological age, compared to individuals with unhealthy lifestyles. Our study indicates that a healthier lifestyle is associated with longer TL in SMD. This highlights the importance of health behaviours as potential clinical targets for ensuring healthier cellular ageing in psychiatric populations.